2000
DOI: 10.1007/s002320001014
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Agonists Inhibit Calcium-Activated Potassium and Voltage-Dependent Sodium Currents in Rat Taste Receptor Cells

Abstract: Recently we reported that rat taste receptor cells respond to the neurotransmitter serotonin with an inhibition of a calcium-activated potassium current [17]. In the present study, this observation is confirmed and extended by studying the effects of an array of serotonergic agonists on membrane properties, calcium-activated potassium current, and voltage-dependent sodium current in taste receptor cells using the patch-clamp recording technique in the whole-cell configuration. Serotonergic inhibition of calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Current was inhibited 26 Ϯ 5% (n ϭ 9) and 39 Ϯ 4% (n ϭ 11) at Ϫ80 and Ϫ50 mV, respectively. These results are similar to inhibition of outward currents in these cells at these same holding potentials produced by serotonin (17). Similar effects of caffeine could be demonstrated with the use of the potassium channel inhibitors TEA and 4-AP.…”
Section: Resultssupporting
confidence: 72%
“…Current was inhibited 26 Ϯ 5% (n ϭ 9) and 39 Ϯ 4% (n ϭ 11) at Ϫ80 and Ϫ50 mV, respectively. These results are similar to inhibition of outward currents in these cells at these same holding potentials produced by serotonin (17). Similar effects of caffeine could be demonstrated with the use of the potassium channel inhibitors TEA and 4-AP.…”
Section: Resultssupporting
confidence: 72%
“…It is known that 5-HT release from taste buds is not dependent on calcium influx but on store release (Huang et al, 2005). (4) We propose a serotonergic feedback from presynaptic to receptor cells where 5-HT acts via 5-HT 1A receptors (Delay et al, 1997;Herness and Chen, 1997;Herness and Chen, 2000;Kaya et al, 2004) to modulate bitter and sweet signaling. In some amphibian taste cells, activation of 5-HT 1A receptors is known to increase intracellular calcium levels (Delay et al, 1997), and 5-HT 1A receptors have been shown to affect intracellular calcium in other cell types (Raymond et al, 1992;Khan et al, 1995).…”
Section: Effects Of Monoamine Manipulation On Taste Perceptionmentioning
confidence: 98%
“…The strongest evidence for an involvement of 5-HT and NA in taste signaling is at the level of the taste bud: taste cells from many species express 5-HT (Nada and Hirata, 1975;Kim and Roper, 1995;Clapp et al, 2004), its synthetic enzymes (DeFazio et al, 2006), and its receptors (Delay et al, 1997), and both take up 5-HT (Nagai et al, 1998) and release it in response to stimulation with tastants (Huang et al, 2005). 5-HT and NA affect taste cell excitability by altering ion channel function (Herness and Chen, 1997;Herness and Chen, 2000;Herness et al, 2002). 5-HT modulates responses in primary gustatory neurons (Esakov et al, 1983), possibly through 5-HT 3 receptors (Zhong et al, 1999;Wang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The final events shown, depolarization leading to transmitter release, remain somewhat speculative that serotonin is a paracrine transmitter at 5-HT1A receptors in taste buds. Serotonin may modulate the threshold of sensory receptor cells in the taste bud or alter membrane properties in taste bud cells [138,139]. Indeed, a recent report from L. Donaldson's laboratory shows selective serotonin re-uptake inhibitors alter human taste thresholds for sweet and bitter via a peripheral mechanism [140].…”
Section: Information Flow In the Taste Budmentioning
confidence: 99%